Institutional Development Paths in Seaports: The Southern African Case - Darren Fraser; Theo Notteboom (European Journal of Transport and Infrastructure Research, 2015)
In the last three decades, transport economists and geographers have published an array of studies on port institutions and governance. Many of these publications emphasize the role of institutions in enabling or inhibiting port efficiencies, port competition (inter and intra) and the development of a port’s resources and capabilities. Political instabilities and their consequential economic lags have to some extent misaligned the pace of institutional reforms in Southern African ports compared with ports in the developed world. Some ports in this region (South Africa, Mozambique, Namibia, Mauritius and Madagascar) have however, over the last 10 to15 years begun to follow the port reform trend, and as such have undergone various degrees of institutional reform. This work seeks to provide a detailed case study which discloses a holistic overview of recent and on-going institutional reforms of Southern African ports from two perspectives. Firstly, by assessing the extent to which institutional structures have shaped and mediated port development in Southern Africa. Secondly, by conducting a port institutional positioning comparison between a range of North European and Southern African container ports in order to determine how similarly Southern African ports resemble more established first world ports. Southern African ports effectively present a unique case of mixed port institutional development trends compared to those in more developed regions of the world. As such, this case study reinforces the fact that different port institutional structures are locally embedded and do matter in port competition, and that institutional reform has supported port development to varying degrees.